1979
DOI: 10.1007/bf00235671
|View full text |Cite
|
Sign up to set email alerts
|

On the central generation of locomotion in the low spinal cat

Abstract: A central network of neurones in the spinal cord has been shown to produce a rhythmic motor output similar to locomotion after suppression of all afferent inflow. The experiments were performed mainly in acute spinal cats (th. 12), which had received DOPA i.v. and the monoamine oxidase inhibitor Nialamide. In some preparations all dorsal roots supplying the spinal cord were transected, in others phasic afferent activity was suppressed by curarization. The activity was recorded as neurograms from nerve filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
356
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 757 publications
(388 citation statements)
references
References 30 publications
22
356
0
1
Order By: Relevance
“…Systemic administration of the noradrenergic precursor, L-DOPA, evokes spontaneous alternating activity of flexors and extensors (see Grillner 1969;Grillner and Zangger 1979). Intracellular motoneuron recordings during L-DOPA induced locomotion revealed strong mutual inhibitory interactions between interneuronal pathways to flexors and extensors (Jankowska et al, 1967a).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of the noradrenergic precursor, L-DOPA, evokes spontaneous alternating activity of flexors and extensors (see Grillner 1969;Grillner and Zangger 1979). Intracellular motoneuron recordings during L-DOPA induced locomotion revealed strong mutual inhibitory interactions between interneuronal pathways to flexors and extensors (Jankowska et al, 1967a).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…During fictive locomotion (e.g., Grillner and Zangger 1979;Jordan, 1991;Turkin and Hamm, 2004;Lafreniere-Roula and McCrea 2005) and treadmill locomotion (Duysens, 1977) in the cat and during the scratch reflex in the turtle (Stein 2005) and the cat (Lafreniere-Roula and McCrea 2005), rhythmic bursts of motoneuron activity can be absent (deleted) for a few cycles. During these deletions activity fails simultaneously in multiple synergist motoneuron pools and becomes tonic in multiple antagonists.…”
Section: Single Level Half-center Models Of the Cpgmentioning
confidence: 99%
“…Furthermore, we suggest that stimulation of trigeminal afferents is analogous to stimulation of segmental afferent pathways in the production of locomotion (Sherrington, 1910;Jankowska et al, 1987;Afelt, 1970;Budakova, 1972;Grillner and Zangger, 1979).…”
mentioning
confidence: 98%
“…Although locomotion can be induced without any sensory input from the periphery (Grillner and Zangger, 1979), extensive studies in lower vertebrates and humans have demonstrated that sensory signals associated with afferents that register hip position, muscle loading, and cutaneous sensation from the foot sole have specific regulatory effects on locomotion (Whelan, 1996;Rossignol et al, 2006). An improved understanding of the physiologic processing of these sensory signals in human spinal cord injury (SCI) is important to the design and implementation of therapeutic interventions for locomotor rehabilitation.…”
Section: Introductionmentioning
confidence: 99%